2014
DOI: 10.1126/scitranslmed.3008051
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Gut Microbe–Host Phenotype Relationships Using Combinatorial Communities in Gnotobiotic Mice

Abstract: Identifying a scalable, unbiased method for discovering which members of the human gut microbiota influence specific physiologic, metabolic and immunologic phenotypes remains a challenge. Here we describe a method in which a clonally-arrayed collection of cultured, sequenced bacteria was generated from one of several human fecal microbiota samples found to transmit a particular phenotype to recipient germ-free mice. Ninety-four bacterial consortia, of diverse size, randomly drawn from the culture collection, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
285
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 330 publications
(301 citation statements)
references
References 52 publications
8
285
0
2
Order By: Relevance
“…Importantly, specific members or subsets of the microbiota can rescue a dearth of Treg or Th17 cells. Although early reports argued that a consortium of Clostridium species from either the murine or human gut is needed to induce Treg cells in the murine colon (5,6), more recent studies showed that an assortment of individual bacterial species, including Clostridium and Bacteroides family members, also possess this property (7,8). Similarly, a single bacterial strain, segmented filamentous bacteria (SFB), is sufficient to drive the accumulation of Th17 cells in the small-intestinal lamina propria (SI-LP) of mice (9,10); however, Th17-inducing microbes derived from the human gut have not yet been identified.…”
mentioning
confidence: 99%
“…Importantly, specific members or subsets of the microbiota can rescue a dearth of Treg or Th17 cells. Although early reports argued that a consortium of Clostridium species from either the murine or human gut is needed to induce Treg cells in the murine colon (5,6), more recent studies showed that an assortment of individual bacterial species, including Clostridium and Bacteroides family members, also possess this property (7,8). Similarly, a single bacterial strain, segmented filamentous bacteria (SFB), is sufficient to drive the accumulation of Th17 cells in the small-intestinal lamina propria (SI-LP) of mice (9,10); however, Th17-inducing microbes derived from the human gut have not yet been identified.…”
mentioning
confidence: 99%
“…Research integrating gnotobiotic mice, dietary variations and mathematical modeling have allowed scientists to predict the effects of diet on the composition of our microbiota and thereby our health 10 . This has wide implications for the growing fields of prebiotics and probiotics.…”
Section: Methods In Microbiome Researchmentioning
confidence: 99%
“…The identification and analysis of the metabolic capacity and phylogeny from these gut microbial communities unfold specific characteristics in healthy and unhealthy subjects (Ramakrishna 2013;Aguirre et al 2014). Therefore, it has been possible to propose a potential causative role for the microbiota in several types of disorders (Faith et al 2014).…”
Section: Introductionmentioning
confidence: 99%